Studi Argumentasi Pembelaan Terhadap Perayaan Maulid Nabi Muhammad SAW Sebagai Sunnah Hasanah - Abd. Samad Baso (Universitas Muslim Indonesia, 2021)
The celebration of the Prophet's birthday is a heretical practice. This statement comes from people who do not understand how to issue laws from the Qur'an and Hadith. Although the celebration of maulid is something new in Islam, it has a foundation from the Qur’an and Hadith. Moreover, in the maulid commemoration, there are many values of obedience, such as gratitude, charity, listening to sermons and the importance of seeking knowledge, listening back to the history and example of the Prophet SAW as a sign of love for the Prophet SAW